2000
DOI: 10.1093/ps/79.7.1033
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Cage Layers

Abstract: Osteoporosis in laying hens is a condition that involves the progressive loss of structural bone during the laying period. This bone loss results in increased bone fragility and susceptibility to fracture, with fracture incidences of up to 30% over the laying period and depopulation not uncommon under commercial conditions. A major cause of osteoporosis is the switch in bone formation from structural to medullary bone at the onset of sexual maturity, but structural bone loss is accelerated by the relative inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
196
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(207 citation statements)
references
References 19 publications
5
196
1
5
Order By: Relevance
“…2). This well vascularized, endosteally formed tissue characteristically has a cancellous or spongy texture and consists of woven bone [9][10][11][12][13] . Endosteal deposits are sometimes caused by disease (for example, avian osteopetrosis) and in such cases they are usually accompanied by bony periosteal outgrowths 13 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). This well vascularized, endosteally formed tissue characteristically has a cancellous or spongy texture and consists of woven bone [9][10][11][12][13] . Endosteal deposits are sometimes caused by disease (for example, avian osteopetrosis) and in such cases they are usually accompanied by bony periosteal outgrowths 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the deposition of avian medullary bone is directly linked to the maturation of the ovarian follicles before egg laying, and that it acts as a calcium reservoir for the production of the calcareous eggshell [9][10][11][12][13][14][15] . The deposition of medullary bone is considered to be an adaptation to compensate for the thin-walled bones of birds, from which extensive bone resorption leads to brittleness and susceptibility to fractures 11,14,15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Welfare issues associated with osteoporosis have become more urgent due to the increasing use of battery cages, which contributes to a decrease in structural bone, leading to bone fragility and susceptibility to fracture [2,13,60]. It has been estimated that bone fragility is responsible for 35% of hen mortalities in caged systems [33], and bone fractures due to production, handling, and transportation have been reported in 29% of birds that reach processing facilities [15] and 98% of birds by the end of the processing line [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, temperature measurements and profiles from IRT images were constructed and compared among housing conditions. Osteoporosis in laying hens is common, and is generally regarded as occurring due to loss of calcium from structural bone to support formation of eggshells over the course of the production cycle [13]. Breakage of leg and wing bones frequently occurs at the end the production cycle when hens are removed from their cages [14,15].…”
Section: Introductionmentioning
confidence: 99%